2010
DOI: 10.1051/0004-6361/201014167
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric observations of comet 67P/Churyumov-Gerasimenko during its 2008–2009 apparition

Abstract: Context. Remote observations of the light scattered by comet 67P/Churyumov-Gerasimenko dust coma are of major importance for determining the physical properties of the particles and prepare the rendezvous with the ESA/Rosetta spacecraft in 2014. Aims. Light scattering and especially linear polarization observations allow comparison between different coma regions and different comets, including comets that have been studied by space probes. Our aim is to retrieve physical properties of the dust particles and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…5 are within the range of values determined for the coma (∼1.35-1.92) within ρ < 100 000 km in February and March, 2009 near perihelion (Lara et al 2011). Hadamcik et al (2010 found that the inner coma of 67P for ρ between 2000 and 8500 km in December 2008 at a heliocentric distance of 1.35 AU had a brightness slope of 1.5, which might be explained in terms of the presence of large and fluffy particles.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…5 are within the range of values determined for the coma (∼1.35-1.92) within ρ < 100 000 km in February and March, 2009 near perihelion (Lara et al 2011). Hadamcik et al (2010 found that the inner coma of 67P for ρ between 2000 and 8500 km in December 2008 at a heliocentric distance of 1.35 AU had a brightness slope of 1.5, which might be explained in terms of the presence of large and fluffy particles.…”
Section: Discussionsupporting
confidence: 78%
“…Hadamcik et al (2010 found that the inner coma of 67P for ρ between 2000 and 8500 km in December 2008 at a heliocentric distance of 1.35 AU had a brightness slope of 1.5, which might be explained in terms of the presence of large and fluffy particles. The similarity to the brightness slopes discussed here might be deceptive because both ground-based results (Lara et al 2011;Hadamcik et al 2010) are for a dust coma much larger than the near-nucleus region and under outgassing conditions very different from the distant coma activity at about 3.5 AU from the Sun (Snodgrass et al 2013). The comparative study of the coma activities of 67P observed by Rosetta at different heliocentric distances (from 3.5 AU to 1.2 AU) in the months to come will probably be the next step for the global investigations of the jet morphology and dynamics.…”
Section: Discussionmentioning
confidence: 70%
“…This high polarization in the inner part can be interpreted by large dark particles, which move slowly. Some comets with an important seasonal effect, as comet 67P/Churyumov-Gerasimenko, may behave like low-P max comets before perihelion and present more jets (with smaller grains) at perihelion or after it (Hadamcik et al, 2010). The presence of large particles (100 m or more) before 2015 perihelion has been confirmed by the first results from COSIMA and GIADA experiments onboard Rosetta spacecraft (e.g.…”
Section: -Introductionmentioning
confidence: 73%
“…When active, the morphology and composition of the coma was constrained by Vincent et al (2013) and Schleicher (2006), respectively; the dust trail was studied by Ishiguro (2008), Kelley et al (2008), Based on observations obtained at the ESO/VLT in the framework of programme 281.C-5004. ; and the polarisation properties of the comet dust were studied by Hadamcik et al (2010). The overall dust environment of the comet coma and tail was studied by Fulle et al (2004), Moreno et al (2004), andFulle et al (2010).…”
Section: Introductionmentioning
confidence: 99%